Antimicrobial activity of metal cation‐exchanged zeolites and their evaluation on injection‐molded pieces of bio‐based high‐density polyethylene. Issue 4 (30th January 2017) - Torres‐Giner, Sergio; Torres, Ana; Ferrándiz, Marcela; Fombuena, Vicent; Balart, Rafael
Abstract: In this study, three different natural types of unmodified zeolite (chabazite, mordenite, and faujasite) were initially characterized for their morphology, elemental composition, and antimicrobial activity against foodborne bacteria and fungi. The chabazite‐type zeolite was selected due to its optimal morphology and lowest silicon to aluminum ratio (Si/Al). This was then solution exchanged with different combinations of silver (Ag + ), copper (Cu 2+ ), and zinc (Zn 2+ ) ions to prepare single, binary, and ternary metal cation‐modified zeolites. Antimicrobial results clearly indicated that Ag‐based zeolites exhibited more antimicrobial activity than Cu‐ and Zn‐based zeolites. Interestingly, the multi‐ionic zeolite, that is, the ternary Ag‐Cu‐Zn‐zeolite, was the most efficient antimicrobial sample in terms of the amount of added silver. In the last step, the obtained multi‐ionic zeolite was, for the first time, incorporated at different weight amounts (1, 5, 10, and 15 wt%) into a bio‐based high‐density polyethylene (bio‐HDPE) matrix by extrusion and shaped into pieces by injection molding. Novel sustainable polymer composite pieces with improved stiffness and hardness and high antimicrobial activity were obtained. These treated materials offer industrial relevance to control the growth of harmful microorganisms in hygiene applications related to the food industry. Practical applications: The here‐developed injection‐molded composite pieces based on green polyethylene and multi‐ionic zeolites showed enhanced mechanical performance and high biocide effect against foodborne bacteria and fungi. Resultant sustainable pieces confirmed good perspectives for their use as functional surfaces capable to control the growth of harmful microorganisms in environments for processing, preparation, and storage of food. Therefore, these novel antimicrobial materials are potential candidates in hygiene applications such as plastic handles, cutlery, rigid packaging, kitchen furnishing, cutting boards, and decontamination surfaces.